2007
DOI: 10.1007/s11243-007-9025-z
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and kinetic studies in aqueous solution on chromium(III) complexes with isocinchomeronic acid—potential new biochromium sources

Abstract: The chromium(III) complexes with a new potential chromium transporting ligand-2,5-pyridinedicarboxylic acid (isocinchomeronic acid, icaH 2 ):[Cr(icaH) 3 ] 0 , [Cr(icaH) 2 (H 2 O) 2 ] + and [Cr(icaH)(H 2 O) 4 ] 2+ (where icaH = N,O-bonded isocinchomeronic acid anion), have been obtained and characterized in solution. The [Cr(icaH) 3 ] 0 complex undergoes aquation in acidic media to the diaquaproduct. Kinetics of this process was studied spectrophotometrically in the 0.1-1.0 M HClO 4 range, at I = 1.0 M. The fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 22 publications
(35 reference statements)
1
19
0
Order By: Relevance
“…They appeared to have increased solubility and reactivity in comparison to analogous picolinic acid derivatives, including the most popular chromium(III) complex, mer-[Cr(pic) 3 ] 0 . Our studies on acid-catalysed aquation of the [Cr(quinH) 3 ] 0 and [Cr(icaH) 3 ] 0 compounds [18,19] revealed that introduction of a second carboxylic group to the pyridine ring of the ligand increases the rate of ligand dissociation. Both complexes could potentially serve as biochromium sources and for that reason should be extensively examined.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…They appeared to have increased solubility and reactivity in comparison to analogous picolinic acid derivatives, including the most popular chromium(III) complex, mer-[Cr(pic) 3 ] 0 . Our studies on acid-catalysed aquation of the [Cr(quinH) 3 ] 0 and [Cr(icaH) 3 ] 0 compounds [18,19] revealed that introduction of a second carboxylic group to the pyridine ring of the ligand increases the rate of ligand dissociation. Both complexes could potentially serve as biochromium sources and for that reason should be extensively examined.…”
Section: Introductionmentioning
confidence: 94%
“…Recently, chromium(III) complexes with quinolinic and isocinchomeronic acids were obtained and characterized in acidic media [18,19]. They appeared to have increased solubility and reactivity in comparison to analogous picolinic acid derivatives, including the most popular chromium(III) complex, mer-[Cr(pic) 3 ] 0 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like Lewis base, it can also act as chelating or multidentate bridging ligand [7]. There were many compounds reported in which M-O and M-N coordination was observed [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…It also accelerates the redox reactions between alcohols and chromic acid [26]. Pyridinedicarboxylic acids also act as chelating agents of chromium, zinc, manganese, copper, iron and molybdenum [7].…”
Section: Introductionmentioning
confidence: 99%